The role of awareness and perceived values upon the acceptance of Islamic Banking in Dagestan - Abduh, Muhamad; Idrisov, Magomed (International Association of Islamic Banks, 2014)
Islamic Banking has been introduced in many countries globally for the last three decades. However, in Russia, Islamic Banking and Finance industry is still in its early stages. The study is aimed at examining the role of awareness and perceived values among Dagestanians upon their acceptance towards Islamic banking. Modified theory of reasoned action model was used to examine the factors affecting Dagestanians’ behavioral intention to patronize Islamic Banking. Information from 400 respondents was extracted using structural equation model. The findings indicated that awareness, although without having fundamental knowledge about Islamic banking, has a positive influence on intention to support Islamic banking via attitude while perceived values have positive influence on intention to support Islamic banking but statistically insignificant.